Invitation to world missions: a Trinitarian missiology for the twenty-first century - Tennent, Timothy C. (Invitation to theological studies, 2010)
Introduction -- Section A: Megatrends that are shaping twenty-first century missions -- From moratorium and malaise to 'selah' and rebirth -- Section B: The Triune God and the Missio dei -- A trinitarian, missional theology -- A trinitarian framework for missions -- God the Father : the providential source and goal of the Missio dei -- Section A: A missional perspective on the Bible -- The God of mission reveals his plan -- The sending Father and the sent church -- Section B: Creation, revelation, and the human response to God's rule -- A trinitarian, "new creation" theology of culture -- An evangelical theology of religions -- God the Son : the redemptive embodiment of the Missio dei -- Section A: Missions history as a reflection of the incarnation -- Turning points in the history of missions before 1792 -- The "great century" of missions, 1792-1910 -- The flowering of world Christianity, 1910-present -- Section B: Cross-cultural communication as a reflection of the incarnation -- The incarnation and the translatability of the Gospel -- Access and reproducibility in missions strategy -- Reflecting the incarnation in holistic missions -- God the Holy Spirit : the empowering presence of the Missio dei -- Section A: Empowering the church to embody the presence of the future -- The Holy Spirit, the book of Acts, and the Missio dei -- The church as the embodiment of the new creation -- Section B: Missionaries as agents of suffering and heralds of the new creation -- The suffering, advancing church -- Conclusion: the church as the reflection of the trinity in the world